Three-dimensional singularity index at interface corner in prismatic butt joint under arbitrary material combination. (15th October 2021) - Miyazaki, Tatsujiro; Fujiwara, Takahiro; Noda, Nao-Aki; Sano, Yoshikazu
Graphical abstract: Highlights: 3D singular indexes at the interface corner in the prismatic butt joint are calculated under all material combinations. The effect of the material combinations on the stress singularity is clarified. 3D singular index is compared with 2D singular index. The simple expression to discriminate the stress singularity at the interface corner is proposed. Abstract: In this paper, the three-dimensional (3D) singularity index at the interface corner λ c o r n e r is newly analyzed for the prismatic butt joint in comparison with the two-dimensional (2D) singularity index along the interface edge λ 2 D previously studied. The finite element eigenanalysis reveals that the ratio of the singularity index is in the range of 0.85 ≤ λ c o r n e r / λ 2 D ≤ 1.15 for the all range of material combination. Under 2D bad pair condition expressed by Dundurs' parameters α, β as α α - 2 β > 0, the ratio is in the range 0.85 ≤ λ c o r n e r / λ 2 D < 1 . The 3D bad pair condition when the singular stress appears at the corner is clarified on the α, β map in comparison with 2D well-known expression α α - 2 β > 0 . Simple and convenient discriminant formula at the 3D interface corner is also indicated for the appearance of the stress singularity.